2023
DOI: 10.1186/s12966-023-01423-3
|View full text |Cite
|
Sign up to set email alerts
|

Development, explanation, and presentation of the Physical Literacy Interventions Reporting Template (PLIRT)

Abstract: Background The physical literacy (PL) concept integrates different personal (e.g., physical, cognitive, psychological/affective, social) determinants of physical activity and has received growing attention recently. Although practical efforts increasingly adopt PL as a guiding concept, latest evidence has shown that PL interventions often lack specification of important theoretical foundations and basic delivery information. Therefore, the goal of the present study was to develop an expert-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…For example, an earlier paper conducted a conceptual critique of three Canadian physical literacy assessment instruments for school-aged children in terms of how well they related to Whitehead’s conception of physical literacy [ 53 ]. Reporting the theoretical standpoint and definition of physical literacy has also been recommended for the reporting of physical literacy interventions [ 69 ]. Even though our focus for this review was school-aged children, physical literacy is a lifespan concept and documenting the validity and reliability of instruments to assess physical literacy in the early years of children and adults are also worthy future endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an earlier paper conducted a conceptual critique of three Canadian physical literacy assessment instruments for school-aged children in terms of how well they related to Whitehead’s conception of physical literacy [ 53 ]. Reporting the theoretical standpoint and definition of physical literacy has also been recommended for the reporting of physical literacy interventions [ 69 ]. Even though our focus for this review was school-aged children, physical literacy is a lifespan concept and documenting the validity and reliability of instruments to assess physical literacy in the early years of children and adults are also worthy future endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been observed that perceived competence acts as a mediator in the relationship between motor competence and physical activity among adolescents 44 45. Thus, the development of PL allows for engagement in lifelong physical activity through improvements in motor skills and cognitive–emotional competencies,46 integrating MF as a construct of ‘motor skills’ found in the definition and assessment of PL 47 48…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the research design with two pilot cycles ( 51 ) accounts for potential pitfalls (e.g., revision of PL content) toward a sound examination of the effectiveness of the PL intervention. The final reporting of study will adhere to the recent physical literacy interventions reporting template suggesting a total of 14 items ( 58 ). The ethics committee of the University of Oldenburg, Germany, has approved the conduction of the study (sign Drs.EK/2022/057).…”
Section: Methodsmentioning
confidence: 99%